Ploidy as a leaky reproductive barrier: mechanisms, rates and evolutionary significance of interploidy gene flow - Bartolić, Paolo; Morgan, Emma J; Padilla-García, Nélida; Kolář, Filip (Annals of botany, 2024)
BACKGROUND: Whole-genome duplication (polyploidization) is a dominant force in sympatric speciation, particularly in plants. Genome doubling instantly poses a barrier to gene flow owing to the strong crossing incompatibilities between individuals differing in ploidy. The strength of the barrier, however, varies from species to species and recent genetic investigations revealed cases of rampant interploidy introgression in multiple ploidy-variable species. SCOPE: Here, we review novel insights into the frequency of interploidy gene flow in natural systems and summarize the underlying mechanisms promoting interploidy gene flow. Field surveys, occasionally complemented by crossing experiments, suggest frequent opportunities for interploidy gene flow, particularly in the direction from diploid to tetraploid, and between (higher) polyploids. However, a scarcity of accompanying population genetic evidence and a virtual lack of integration of these approaches leave the underlying mechanisms and levels of realized interploidy gene flow in nature largely unknown. Finally, we discuss potential consequences of interploidy genome permeability on polyploid speciation and adaptation and highlight novel avenues that have just recently been opened by the very first genomic studies of ploidy-variable species. Standing in stark contrast with rapidly accumulating evidence for evolutionary importance of homoploid introgression, similar cases in ploidy-variable systems are yet to be documented. CONCLUSIONS: The genomics era provides novel opportunity to re-evaluate the role of interploidy introgression in speciation and adaptation. To achieve this goal, interdisciplinary studies bordering ecology and population genetics and genomics are needed.
Keywords: Genetic Speciation; Plants; polyploidy; speciation; Genome, Plant; genom rostlinný; whole-genome duplication; Reproduction; tok genů; Adaptation; ploidie; biologická evoluce; vznik druhů (genetika); rozmnožování; rostliny; genetic introgression; Biological Evolution; evolution; Polyploidy; Ploidies; polyploidie; Gene Flow